Dynamic of sediment transport capacity by overland flow: a review - Siti Norhafizah Hamizak; Zuliziana Suif; Jestin Jelani; Nordila Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2024)
This paper systematically reviews the relationship between sediment transport capacity and factors such as flow velocity, slope gradient, hydraulic parameters, soil properties, and root parameters in overland flow. The aim of this paper is to investigate the relationship between the sediment transport capacity on flow velocity, slope gradient, hydraulic parameters, soil properties, and root parameters on sediment transport capacity by overland flow and to evaluate the research findings for improving the accuracy of sediment transport predictions. A total of 36 journal articles from 2019 to 2024 were eligible through conducted Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) method protocol. The review identifies that each factor significantly influences sediment transport capacity. Increased flow velocities and steeper slopes generally enhance sediment transport by providing more energy and higher runoff velocity. Hydraulic parameters, including flow depth and discharge rate, are critical, with greater depths and faster flows increasing transport potential. Soil properties, like texture and cohesion, affect sediment detachment and transport, with sandy soils typically showing lower transport rates than clayey soils under similar hydraulic conditions. Root parameters, such as root density, diameter, depth, and biomass, contribute to soil stabilization and reduce sediment transport by improving soil structure and increasing resistance to erosion. The review underscores the importance of considering the combined effects of these factors, which often result in complex interactions impacting sediment transport. Identified research gaps suggest the need for models integrating these interactions to improve predictive accuracy. Addressing these gaps can enhance sediment transport models, informing better soil conservation strategies and erosion control measures.